The Effectiveness of Click and Clunk Strategy on the Students’ Reading Achievement - Annisa Rahmasari; Varia Virdania Virdaus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
The goal of this study is to determine how well the Click & Clunk approach works in improving students' reading comprehension. In this study, non-randomized pretests and posttests were used in a quasi-experimental setting utilizing quantitative methodologies. Students from SMPN 1 Kanigoro served as the study's subjects, with Class 7H serving as the control group and Class 7I serving as the experimental group. Reading assessments served as the research's tools (pretest and posttest). The control group class, on the other hand, was taught using the KWL method. The experimental group class was taught utilizing the Click & Clunk method. A posttest was then provided to both groups. The data was generated by SPSS Version 20 and then analyzed using ANCOVA. The analysis's findings suggested that the Click and Clunk Strategy could raise children' reading proficiency.